The experience of patients with breast cancer at home during chemotherapy treatment: a qualitative approach - Sarkarsi, Rosnani; Syed Elias, Sharifah Munirah; Lee, Siew Pien (IIUM Press, 2023)
Introduction: Cancer is the primary cause of death worldwide and a significant barrier to increasing life expectancy. The estimates from World Health Organization (WHO) in 2019, cancer is the first or second leading cause of death before the age of 70 in 112 of 183 countries and ranks mortality third or fourth in 23 countries. Patients with breast cancer in Malaysia have one of the lowest survival rates in the Asia-Pacific region, with a 5-year survival of only 49%, compared with up to 90% in the United States. Chemotherapy is a type of cancer treatment that uses one or more anti-cancer drugs as part of a standardized chemotherapy regimen. It may be given with a curative intent (which almost involves combinations of drugs), or it may aim to prolong life or reduce symptoms (palliative). The challenges for the patient in dealing with the side effects of the chemotherapy treatment begin while they are at home. Objective: To explore the experience of patients with breast cancer at home during chemotherapy treatment. Methods: This study employed a qualitative research design involving 20 patients with breast cancer undergoing chemotherapy treatment. The participants were recruited via purposive sampling and data were collected by semi-structured interview with recorded. The thematic analysis approach was used to analyze the data. Results: Two themes were revealed: including emotional changes and physiological changes. This theme revealed the preference described by emotional changes with the explanation of physiological changes. Conclusion: Patients with breast cancer not only experience the side effects of chemo drugs but also have to deal with the changes at home during chemotherapy treatment. There is a need for healthcare workers in Malaysia to be able to provide support, especially in terms of emotional and physiological support at home for patients with breast cancer.